2018
DOI: 10.1080/1354750x.2017.1419284
|View full text |Cite
|
Sign up to set email alerts
|

Review of biomarkers to assess the effects of switching from cigarettes to modified risk tobacco products

Abstract: In clinical studies, it is important to choose biomarkers that show the biological effect of cessation within the duration of the study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 559 publications
(557 reference statements)
1
13
0
Order By: Relevance
“…As with the BoExp, the dose-response seen in the primary endpoints in the present study, in particular when exposure reduction is further improved by predominant THS users abstaining from cigarette smoking, are consistent with effects seen in smoking cessation (17,18,27) but also in smokers who reduced their daily cigarette consumption (28)(29)(30).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…As with the BoExp, the dose-response seen in the primary endpoints in the present study, in particular when exposure reduction is further improved by predominant THS users abstaining from cigarette smoking, are consistent with effects seen in smoking cessation (17,18,27) but also in smokers who reduced their daily cigarette consumption (28)(29)(30).…”
Section: Discussionsupporting
confidence: 81%
“…They also reflect the adverse health effects of HPHCs that affect multiple organ systems, disease pathways, and mechanisms (15,16). Each primary endpoint was identified through a review of the existing science (17,18).…”
Section: Rationale For Biomarker Selectionmentioning
confidence: 99%
“…These biomarkers provide information to policymakers during the assessment of health risks associated with new and modified tobacco products 28. Several biomarkers exist for conventional tobacco products; however, biomarkers specific for WP, smokeless tobacco products or other modified-risk tobacco products have not been well established 29 30. We report, for the first time, the differential expression of immediate-early genes (IEG) upregulated in the lung after acute exposure to WP and dry smoke (with no water in the bowl).…”
Section: Introductionmentioning
confidence: 93%
“…In a literature review, Scherer (2018) stated that there was uncertainty regarding the recovery time of 8-epi-PGF2a after quitting smoking. Moreover, another literature search by Peck et al (2018) indicated that there was no substantial evidence of a strong direct link between 8-iso-PGF2a and smoking cessation except where a long period of time had elapsed. Our results and the other reports suggest that a reduction in cigarette smoke exposure affects the level of 8-epi-PGF2a, but the recovery time to NS levels has still not been clarified.…”
Section: Differences In Boph At Day 28/29mentioning
confidence: 99%